The use of Egyptian spoken Arabic in modern Egyptian novels - Essa, Esraa (AUC Knowledge Fountain, 2016)
Modern Standard Arabic (MSA) is the language of novels and written literature and is thus defined as a “High” variety. Nevertheless, young Egyptian authors of the new generation prefer to use a mix between Egyptian colloquial Arabic (ECA) and MSA as a medium for creating a new spirit in novels. In fact, the sharp lines between (MSA) and colloquial Egyptian (ECA) in the Modern Egyptian Novels have begun to blur (Badawi, 1973; 2012). Badawi (1973) proposed a five-level continuum in which each level gradually merges into the next. Arabic in Egypt encompasses five levels of language: (fusha al-turath and Qur’an) Classical Arabic, Modern Standard Arabic, ('ammiyyat al-muthaqqafiin), Colloquial of the cultured, ('ammiyyat al-mutanawwriin) Colloquial of the basically educated and ('ammiyyat al-ummiyyiin) Colloquial of the Illiterate). The present study aims at answering the following research questions: 1. What variety of Arabic is used in the narration of Modern Egyptian Novels in the two novels under investigation? 2. What are the NMSA patterns and their linguistics structures, and in which domains they are used in the narration of the two novels under investigation? The results show that the language of the narration of the two novels under investigation was not exclusively MSA; rather, it features numerous NMSA insertions of different patterns and from different domains. Finally, the contribution of this study is to interpret the mix of the different Arabic varieties as defined by Badawi (1973; 2012) in some Contemporary Egyptian novels. Understanding this phenomenon helps teachers of Arabic as a foreign language to acquire a more realistic picture of the varieties used in novels. This heightened knowledge also enriches the ability of teachers of Arabic to reflect and provide appropriate explanations of such a picture to their students.